Analysis of the Early Reading Learning Outcomes of Children Aged 5–6 Years Through a Computational Thinking-Based Problem-Based Learning Model - Isrofinatun Nahari Magfiroh; Ifa Aristia Sandra Ekayati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Early reading skills are one of the essential aspects of early childhood language development that need to be developed as a foundation for entering the next level of education. This study aimed to analyze the early reading learning outcomes of children aged 5–6 years through a Computational Thinking-based Problem-Based Learning (PBL) model. The study employed a quantitative approach using a one-group pretest-posttest design. The research subjects consisted of 15 children in Group B at TK PGRI Tunas Harapan Keduyung, selected using a purposive sampling technique. Data were collected through observation using an instrument covering early reading indicators and were analyzed using descriptive statistics by calculating the mean scores, percentages, and developmental categories of children's learning outcomes. The results showed that the average early reading learning outcome at the pretest stage was 7 (43.75%), which was categorized as Beginning to Develop (BD). After the implementation of the Computational Thinking-based Problem-Based Learning model, the average learning outcome increased to 12 (75%), which fell into the category of Developing as Expected (DE). The findings indicate that children's early reading learning outcomes through the Computational Thinking-based Problem-Based Learning model reached the Developing as Expected (DE) category. Therefore, the Computational Thinking-based Problem-Based Learning model can be used as an alternative instructional approach to support the achievement of early reading learning outcomes in early childhood.